Future U.S. security relationships with Iraq and Afghanistan : U.S. Air Force roles - Thaler, David E. (Rand Corporation monograph series., 2008)
"The United States is heavily invested -- diplomatically, economically, and militarily -- in Iraq and Afghanistan, and developments in these two nations will affect not only their own interests but those of their neighbors and the United States as well. The authors emphasize that the United States must clarify its long-term intentions to the governments and peoples in Iraq, Afghanistan, and the surrounding regions. They describe possible regional security structures and bilateral U.S. relationships with both countries. The authors recommend that the United States offer a wide range of security cooperation activities to future governments in Kabul and Baghdad that are willing to work with the United States but should also develop plans that hedge against less-favorable contingencies. Finally, arguing that the U.S. Air Force could remain heavily tasked in Iraq and Afghanistan even after major U.S. troop withdrawals, they recommend that the United States provide increased, sustained resources for development of the Iraqi and Afghan airpower, because the greater the emphasis on building these capabilities now, the faster indigenous air forces will be able to operate independently and the operational demands on the U.S. Air Force will diminish."--Publisher's website